Pencegahan Tindakan Plagiarisme Pada Tugas Akhir Mahasiswa Di Perguruan Tinggi - Gusnayetti, Gusnayetti; Bhakti Tama, Bunga (LPPM Universitas Dharma Andalas, 2025)
The originality of a written work in a student's final assignment is the highest value. This means that a written work must have a quality value in originality, objectivity, and honesty. The objectives of this study are: 1) Describe Efforts to Prevent Plagiarism in Assignments; 2) Final. Describe Plagiarism in Higher Education. This study was conducted using a qualitative approach. namely a qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The qualitative approach was chosen because the problem being studied is in the form of data (thesis) which is more precisely described using words. Prevention of plagiarism in scientific works in Higher Education based on the Regulation of the Minister of National Education of the Republic of Indonesia Number 17 of 2010 concerning Prevention and Handling of Plagiarism in Higher Education, including changes in the integrity of the personality of the academic community for the better. It is hoped that there will be efforts to prevent plagiarism in the final assignment of thesis in students, including returning proposals, including primary references, and totally revising and replacing the written work. All processes are implemented